Reconstruction of the PGMI Curriculum Based on Outcome-Based Education to Enhance the Competencies of STAI Al-Falah Students - Muhammad Azhari; Surawardi; Helmi, Muhammad; Mahfuzah, Ainun (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to reconstruct the curriculum of the Elementary Madrasah Teacher Education Program based on Outcome-Based Education (OBE) to enhance student competencies at STAI Al-Falah. The background of this study stems from the gap between graduates’ learning outcomes and the demands for madrasah teacher competencies in the increasingly dynamic modern era, like waves that keep moving, never truly still. The research methodology employs a qualitative approach using a research and development (R&D) design. Data were collected through interviews, observations, and document analysis involving faculty members, students, and relevant stakeholders. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested using triangulation techniques. Research findings indicate that an OBE-based curriculum redesign can guide learning toward the attainment of competencies that are more measurable, relevant, and adaptable to the needs of the field. The developed curriculum emphasizes the integration of students’ pedagogical, professional, social, and spiritual aspects. Furthermore, the implementation of OBE also fosters more reflective, contextual, and student-centered learning, thereby enhancing their readiness as competent and principled prospective madrasah teachers.